THE EFFECT OF GLOBAL ECONOMIC IMBALANCES ON THE MILITARY STRATEGY OF THE UNITED STATES AND CHINA (Journal of the Spanish Institute for Strategic Studies, 2018)
The current account deficit of the U.S. has increased considerably since the beginning of the century and China has made a major contribution to this deficit due to its export-driven growth process. The deficit is unsustainable in the medium and long run and the Chinese economy is beginning to change its pattern. As a consequence, the military strategy of the United States will undergo major changes that will affect the balance of power with China